When Do Women Speak? A Comparative Analysis of the Role of Gender in Legislative Debates. (August 2019) - Bäck, Hanna; Debus, Marc
Do female representatives participate less often in legislative debates, and does it matter which topic is debated? Drawing on the role incongruity theory, we hypothesise that women take the parliamentary floor less often because of the gender stereotypes that are likely to guide the behaviour of party representatives. Such underrepresentation is less likely to be present when debates are dealing with policy areas that can be characterised as feminine. By referring to critical mass theory, we expect women to participate less in debates if they are members of parties with fewer female representatives. The results of an analysis of speechmaking among members of parliament in seven European countries show that female members of parliament are less represented in legislative debates, especially when debates deal with topics that can be characterised as masculine. Furthermore, the effect of gender on speechmaking clearly varies across parties. However, the pattern does not follow the logic derived from critical mass theory. Instead, female members of parliament take the floor less often when they are members of parties with many female representatives.